Epistemology in Islam: A Philosophical Study - Ogaba, Isenyo Solomon (Universitas Negeri Makassar, 2021)
This work attempts to expose Quranic epistemology and the views of prominent Muslim scholars (Ghazzali and Ibn Rushd) is been discussed. The impact of Ghazzali was profound on Sufism, jurisprudence, Muslim theology, philosophy, and almost all other disciplines and a lot of research has been done on these aspects of Ghazzali. But so far as the epistemology of Ghazzali is concerned, very little is known about it. Same as Ibn Rushd who is also a Muslim scholar of repute; widely known in the field of epistemology. Works of literature existing on both Ghazzali and Ibn Rushd focused on the individual contribution of each of these scholars on religion and other areas of endeavour, except Islamic epistemology. Furthermore, there is no study available on the comparison of the epistemology of Ghazzali with that of Ibn Rushd and vice-versa. Thus, a detailed study of the epistemological theories of these two stalwart thinkers of Islamic history is of great significance whose impact was epoch-making and clandestine on east and west respectively. The attempt to find out and explore whether there is any room for reconciliation between these two scholars is also of great relevance.